Case series of 21 patients with extrahepatic metastatic lobular breast carcinoma to the gastrointestinal tract. (2015) - Switzer, Noah; Lim, Andrew; Du, Lillian; Al-Sairafi, Rani; Tonkin, Katia; Schiller, Dan
Abstract: Background: Invasive lobular carcinoma (ILC) comprises 5–16% of all breast cancers, with its incidence gradually increasing. ILC has a disproportionately higher incidence of spread to the gastrointestinal (GI) system. Methods: This study is a retrospective chart review of all cases of ILC with gastrointestinal metastases seen at a university affiliated tertiary cancer institute between 2005 and 2010, examining demographic, epidemiological, medical, and treatment factors that may have an association with the risk of GI metastases. Results: 343 consecutive cases of lobular breast cancer were reviewed, and 21(6%) were found to have GI metastases. The mean age at initial diagnosis of primary tumor was 63 years. Stages at presentation of the breast primary were: Stages 1/2%=73% and stages 3/4=27%. Receptor status of the primary breast cancer was as follows: HER2+=5%, PR+=76%, ER+=90%. The mean age at time of diagnosis of metastatic disease was 67 years. The main presenting symptoms of GI metastatic disease were: incidental finding/asymptomatic (20%), nausea (20%), and abdominal pain (15%). The major sites of extrahepatic gastrointestinal spread were the stomach (52%), peritoneum (38%), and omentum (19%). Average five-year survival from initial diagnosis of ILC was 46%. Five-year survival from diagnosis of gastrointestinal metastasis was 29%. Conclusions: Approximately 1 in 20 patients diagnosed with ILC will have spread to the GI tract, presenting 4 years after their initial primary diagnosis. Future research is needed in developing treatment regimens for these patients, as the 5-year survival is only approximately 1 in 4.